Integrated partial match query in Geographic Information Retrieval - Zainol, Rosilawati; Bakar, Zainab Abu; Ali, Sayed Jamaludin (Universiti Putra Malaysia, 2011)
This paper presents the evaluation of integrated partial match query in Geographic Information Retrieval (GIR). To facilitate the evaluation, Kuala Lumpur tourist related data is used as test collection and is stored in SuperWeb, a map server. Then the map server is customized to enhance its query capability to recognize word in partial or case sensitive between layers of spatial data. Query keyword is tested using the system and results are evaluated using experiments on sample data. Findings show that integrated partial match query provides more flexibility to tourist in determining search results. © Universiti Putra Malaysia Press.